Hepcidin secretion was not directly proportional to intracellular iron-loading in recombinant-TfR1 HepG2 cells: short communication - Kosha J. Mehta; Mark Busbridge; Vinood B. Patel; Sebastien Je. Farnaud (Molecular and Cellular Biochemistry, 2020)
Hepcidin is the master regulator of systemic iron homeostasis and its dysregulation is observed in several chronic liver diseases. Unlike the extracellular iron-sensing mechanisms, the intracellular iron-sensing mechanisms in the hepatocytes that lead to hepcidin induction and secretion are incompletely understood. Here, we aimed to understand the direct role of intracellular iron-loading on hepcidin mRNA and peptide secretion using our previously characterised recombinant HepG2 cells that over-express the cell-surface iron-importer protein transferrin receptor-1. Gene expression of hepcidin ( HAMP ) was determined by real-time PCR. Intracellular iron levels and secreted hepcidin peptide levels were measured by ferrozine assay and immunoassay, respectively. These measurements were compared in the recombinant and wild-type HepG2 cells under basal conditions at 30 min, 2 h, 4 h and 24 h. Data showed that in the recombinant cells, intracellular iron content was higher than wild-type cells at 30 min (3.1-fold, p < 0.01), 2 h (4.6-fold, p < 0.01), 4 h (4.6-fold, p < 0.01) and 24 h (1.9-fold, p < 0.01). Hepcidin ( HAMP) mRNA expression was higher than wild-type cells at 30 min (5.9-fold; p = 0.05) and 24 h (6.1-fold; p < 0.03), but at 4 h, the expression was lower than that in wild-type cells ( p < 0.05). However, hepcidin secretion levels in the recombinant cells were similar to those in wild-type cells at all time-points, except at 4 h, when the level was lower than wild-type cells ( p < 0.01). High intracellular iron in recombinant HepG2 cells did not proportionally increase hepcidin peptide secretion. This suggests a limited role of elevated intracellular iron in hepcidin secretion.